PENINGKATAN RELIGIUSITAS MAHASISWA MELALUI PENDIDIKAN PESANTREN - Tri Wijayanti, fita (El-Hamra, 2019)
Students are considered as agents of change who understood that the student is an intermediary or representative of society towards change. As an agent of change there must be a sense of responsibility to continue to forge themselves, learn a lot of things for the future of themselves and society. One that can be done by the students to learn a lot of things are learned in boarding school. Islamic Schools is one of the non-formal educational institutions and the oldest educational institutions in Indonesia. Islamic Schools is a traditional educational institution whose activity is to learn, understand, appreciate and practice the teachings of Islam with an emphasis on the importance of religious morals to guide everyday behavior. Being a student and also the students certainly not a light thing, to be able to divide their time between college and boarding school. However, pesantren indirectly much to contribute greatly to the students, such as: providing skills, informal leadership, service-oriented expertise, inventive (inventive), and can increase creativity. Key Words: student, education, boarding school